The ectomycorrhizas of Shorea leprosula (dipterocarpaceae). - Su See, Lee (Forest Research Institute Malaysia, 1988)
Roots of 3 year-old and 2 year- old Shorea leprosula seedlings growing in the understorey of an undisturbed forest plantation (site A) and a relatively disturbed lowland rainforest (site B) respectively, were examined for presence of ectomycorrhizas. Soil chemical properties of the two sites were also analysed. Six types of ectomycorrhizas (A-F) and two type of mycorrhiza-like roots (G,H) are described and illustrated. Total infection levels were found to be significantly higher at site B (92.7%) than at site A (76.2%) although the relative abundance of the six mycorrhizal types followed a similar trend at both sites. However, there was a higher incidence of type D at site B while type E was more abundant at sote A. These differences were probably due to the lower levels of phosphorus, nitrogen and potassium at site B. There was no significant relationship between the total infection or infection by each mycorrhiza and either shoot height or shoot dry weight even though the total percentage infection level ranged from 56.5% to 100% and individual infection levels ranged from 0% to 100%. It was obvious that forest seedlings became infected inconsiderably less than two years and that there is no shortage of inoculum potential in the forest.